Effective Hamiltonian and excitation spectrum of harmonically trapped bosons - Rovenchak, A. (Физика низких температур, 2016)
An approach is proposed to obtain an effective Hamiltonian of a harmonically trapped Bose-system. Such a
Hamiltonian is quadratic in the creation–annihilation operators and certain approximations allow to simplify
higher (three and four operator) products to the required form. After the Hamiltonian diagonalization, the expression
for the excitation spectrum is obtained containing in particular temperature-dependent corrections. Numerical
calculations are made for a one-dimensional system. Some prospects towards the extension of the suggested
approach to study binary bosonic mixtures are briefly discussed.